Al-istiarah in the Novel al-Zikrayat by Ali al-Tantawi based on relevant theory - Taj Rijal Muhamad Romli (Tanjong Malim, 2021)
Al-istiarah in the Novel al-Zikrayat by Ali al-Tantawi based on relevant theory by Taj Rijal Muhamad Romli